Understanding and Assessing STEM Teachers’ Use of IBL to Address Achievement-Related Diversity: A Case Study from Turkey - Kaya, Gökhan; Şardağ, Metin (ISRES Publishing, 2021)
This study investigates how STEM teachers use inquiry-based learning (IBL) to address achievement-related diversity in their classroom practices. Data were collected from three teachers who participated in a long-term in-service teacher training program. Teachers' views were elicited through interviews, in-class observation, and evaluation forms. The data obtained were used in a narrative structure to create a detailed case study of each teacher and compare them. It has been determined that some strategies emphasize the diversity of success in IBL activities stand out more. Although these strategies are different, they enable IBL to progress in regularly and enable them to address the diversity of success in the classroom. The lack of a wide variety of strategies used by teachers can be seen as one of the crucial problems in case studies. In particular, the use of methods that will lead to better use of time in the classroom by using out of group work and evaluating them in terms of successful diversity may appear to be an improvement in terms of achieving the desired goals.
Keywords: Özel Eğitim ve Engelli Eğitimi; inclusive education; STEM; inquiry based learning; teacher training; Special Education and Disabled Education; 4. Education